Strategi Pengembangan Usaha Kerajinan Eceng Gondok (Studi Kasus Usaha Kreatif Kerajinan di Cirata Eceng Craft (Ciecra)) - Sukmawati, Hani; Suminartika, Eti (Universitas Galuh, 2024)
Water pollution, stemming from water hyacinth, impedes the essential penetration of sunlight vital for aquatic biota. UMKM Cirata Eceng Craft (CIECRA) is a pioneering creative business active in the water hyacinth industry. Regrettably, business growth has been hindered due to ineffective technology utilization, insufficiently skilled human resources, a lack of digital marketing implementation, and the absence of a strategically centralized production facility. This research seeks to assess the status of the Cirata Eceng Craft Creative Business (CIECRA) and formulate a development strategy for the enterprise. The research methodology employed a qualitative approach utilizing case study techniques, entailing data collection through observation, interviews, and literature review. Key internal and external factors were identified to develop alternative business strategies aligned with the SWOT matrix, quantified using the QSPM matrix. The research findings reveal that the primary strengths of CIECRA MSMEs are their eco-friendly products and active participation in exhibitions/bazaars. Conversely, the scarcity of skilled human resources represents a major weakness. The emergence of e-commerce and social media as marketing platforms poses both an opportunity and a threat, as numerous similar businesses have already entered these arenas. Presently, CIECRA MSMEs occupy quadrant V, indicating the growth and development phase. In line with the outcome of the SWOT analysis, we propose four key strategies: 1) Optimization of online marketing through establishing a dedicated marketing division, 2) Consumer education on eco-friendly products via collaboration with influencers or social media video campaigns, 3) Exploration of alternative markets or business models to achieve broader segmentation, and 4) Investment in research and product development in partnership with relevant government agencies to foster innovation.